DEVELOPMENT OF VOCATIONAL MATERIAL LEARNING MEDIA FOR MATERIAL X CLASS - Atik Restyowati (Universitas Islam Balitar, 2018)
This study aims to determine the three-dimensional media feasibility of virus material in class x. This type of research is Research and Development (R & D) with the development model Brog & Gall. This research through assessment by media experts with an average score of 74.87% with a very feasible category. The research from material experts got an average score of 93.5% with a very decent category. Assessment of teacher responses gets a score of 82.10% with a very decent category. Assessment of student responses is 80.46% with a very good category. Readability test scores get a score of 89.2% with a decent category. Media maket on viral material is very feasible to use for learning in the classroom.